Tuberculosis in Early Infancy: Rare in Today’s World - Thakur, Jitendra; Rai, Basant; Singh, Rupa Rajbhandari; Ghosh, Sohini; Gyawali, Pratyush (Journal of Nepal Paediatric Society, 2019)
Tuberculosis in early infancy was not so common earlier also and has become rare these days. Since the disease is occasionally encountered, pediatricians should suspect tuberculosis in infants not responding to standard therapy. Here we report a case of three months old female who had presented with complaints of fever for two months, cough for one and half months and difficulty breathing for seven days and was being treated in line of bacterial pneumonia without improvement. She was found to be mycobacterium positive and was treated with anti-tubercular therapy leading to improvement and discharge. So, though rare, it is important to consider tuberculosis even in early infancy not responding to standard antibiotic therapy.